2019
DOI: 10.1089/acm.2018.0310
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Food Immunoglobulin G-Based Elimination Diet on Subsequent Food Immunoglobulin G and Quality of Life in Overweight/Obese Adults

Abstract: Objectives: The goal of this study was to assess changes in serum immunoglobulin G (IgG) food antibody titers and quality-of-life measurements following a targeted elimination diet in overweight/obese adults. Methods: We performed a randomized control trial. Participants were randomized in a 2:1 ratio to either an intervention group or waitlist group for 3 months. Food IgG testing was performed on all participants. The intervention group was instructed to eliminate up to 10 foods, for which they had high titer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 23 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…[22,25,59] In addition, for those patients with inflammatory conditions, positive changes in immune responses measured through serum IgG food antibodies and peak eosinophil counts have been used to suggest a beneficial health impact of the elimination diet. [23,25] However, a targeted elimination diet that recognizes and removes food triggers may not only help alleviate disease-specific symptomatology, it may also help to both reduce hyperactive immune responses and to support healthy microbiome composition and function. [20][21][22][23][24][25][59][60][61] In addition, the systematic elimination and reintroduction of foods in an elimination diet can be helpful in identifying foods that may be causing subclinical inflammation and other relatively mild adverse reactions that may collectively impair quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[22,25,59] In addition, for those patients with inflammatory conditions, positive changes in immune responses measured through serum IgG food antibodies and peak eosinophil counts have been used to suggest a beneficial health impact of the elimination diet. [23,25] However, a targeted elimination diet that recognizes and removes food triggers may not only help alleviate disease-specific symptomatology, it may also help to both reduce hyperactive immune responses and to support healthy microbiome composition and function. [20][21][22][23][24][25][59][60][61] In addition, the systematic elimination and reintroduction of foods in an elimination diet can be helpful in identifying foods that may be causing subclinical inflammation and other relatively mild adverse reactions that may collectively impair quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…[23,25] However, a targeted elimination diet that recognizes and removes food triggers may not only help alleviate disease-specific symptomatology, it may also help to both reduce hyperactive immune responses and to support healthy microbiome composition and function. [20][21][22][23][24][25][59][60][61] In addition, the systematic elimination and reintroduction of foods in an elimination diet can be helpful in identifying foods that may be causing subclinical inflammation and other relatively mild adverse reactions that may collectively impair quality of life. Further studies are warranted to confirm the positive impact of an elimination diet on patient-reported health and quality of life metrics in other relatively healthy populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other studies could not detect an association between high levels of IgG to certain food and clinical symptoms (99,100). Moreover, an elimination diet based on results of IgG testing failed to improve IBS symptoms significantly better as compared to patients on a waiting list (101), questioning the validity of this approach. Finally, large exclusion diets harbour a risk of nutritional deficiencies as revealed by studies in patients with documented food allergy (102,103).…”
Section: First-line Approachmentioning
confidence: 98%